2016
DOI: 10.1002/prep.201600158
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment of Ammunition: the Importance of a Life‐Cycle Approach

Abstract: Environmental research related with military actions has been focused on the monitoring of contaminants from live‐fire training and munitions disposal. It is important to take a further step and use this information to assess the environmental impacts of this contamination. In addition, it is relevant to assess the consequences of using different alternatives in a life‐cycle perspective to avoid unexpected problems, and assess the hotspots of ammunition manufacturing in order to decrease the impacts in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Ahmed et al [64] concluded that economic growth played a vital role in reducing military arms transfers and carbon emissions and encouraged efficient energy investment to achieve green developmental objectives worldwide. Ferreira et al [65] argued whether green ammunition lowers environmental challenges to reduce economic sufferings? The lifecycle assessment of warheads emphasized concentrating on production and assessment of ammunition technologies to lower environmental concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al [64] concluded that economic growth played a vital role in reducing military arms transfers and carbon emissions and encouraged efficient energy investment to achieve green developmental objectives worldwide. Ferreira et al [65] argued whether green ammunition lowers environmental challenges to reduce economic sufferings? The lifecycle assessment of warheads emphasized concentrating on production and assessment of ammunition technologies to lower environmental concerns.…”
Section: Resultsmentioning
confidence: 99%
“…[23] To the development of novel promising primaries, which not only requests free from toxic metals but also chemically and thermally stable, better performance, reasonably sensitive, and safe to synthesized. [33] Based on these reasons, synthesis of novel promising metal-free greener primary explosives (consists of only CHON elements) with high performance is required to substitute the LA and LS. [34] Therefore, this paper needs to summarize the latest developments in the synthesis and characterization of various metal-free green primary explosives.…”
Section: Metal-free Modern Primary Explosivesmentioning
confidence: 99%
“…In the past, DDNP and GNGT were considered metal‐free primary explosives, but GNGT exhibits poor pressure resistance and are eliminated from practical applications, while DDNP has major drawbacks such as photosensitivity, high sensitivity to friction, and impact [23] . To the development of novel promising primaries, which not only requests free from toxic metals but also chemically and thermally stable, better performance, reasonably sensitive, and safe to synthesized [33] . Based on these reasons, synthesis of novel promising metal‐free greener primary explosives (consists of only CHON elements) with high performance is required to substitute the LA and LS [34] .…”
Section: Metal‐free Primary Explosivesmentioning
confidence: 99%
“…Both the manufacturers and users of explosives are responsible for any adverse impacts on the environment from explosives by legislation such as the Contaminated Land (England) Regulations 2006 (2), Water Resources Act 1991 (3) and the Environmental Permitting Regulations 2010 (4). Therefore, environmental management systems such as ISO14001 and other environmental assessment tools such as lifecycle analysis (ISO140040) have become a ubiquitous way for organisations to ensure compliance with environmental legislation, and mitigate or minimise their environmental impact through life (5)(6)(7). This is equally true for private business and government organisations, where bespoke management systems have been developed (8).…”
Section: Introductionmentioning
confidence: 99%
“…Adverse impact on the environment from explosive manufacturing and training activities is usually determined by a qualitative process such as environmental impact prioritisation, in which a matrix is used to prioritise significant impacts based on the likelihood and severity (7)(8)(9). The aim of the prioritisation is to indicate the likely significant environmental impacts of an organisation's activities, and highlight where mitigation of adverse impacts is required (10).…”
Section: Introductionmentioning
confidence: 99%